2013
DOI: 10.1155/2013/640723
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran, Rivaroxaban, or Apixaban versus Warfarin in Patients with Nonvalvular Atrial Fibrillation: A Systematic Review and Meta-Analysis of Subgroups

Abstract: Background. New oral anticoagulants (NOAC; rivaroxaban, dabigatran, apixaban) have become available as an alternative to warfarin anticoagulation in non-valvular atrial fibrillation (NVAF). Methods. MEDLINE and CENTRAL, regulatory agencies websites, clinical trials registers and conference proceedings were searched to identify randomised controlled trials of NOAC versus warfarin in NVAF. Two investigators reviewed all studies and extracted data on patient and study characteristics along with cardiovascular out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 59 publications
5
101
0
8
Order By: Relevance
“…All of these agents, and others in development, are under investigation for the management of multiple thromboembolic disorders. [3][4][5][6][7][8][9][10] Dabigatran is an oral direct inhibitor of thrombin (factor IIa) that is ''not permanent,'' selective, and competitive. Rivaroxaban and apixaban are oral direct inhibitors of factor Xa and are also competitive, selective, and not permanent.…”
mentioning
confidence: 99%
“…All of these agents, and others in development, are under investigation for the management of multiple thromboembolic disorders. [3][4][5][6][7][8][9][10] Dabigatran is an oral direct inhibitor of thrombin (factor IIa) that is ''not permanent,'' selective, and competitive. Rivaroxaban and apixaban are oral direct inhibitors of factor Xa and are also competitive, selective, and not permanent.…”
mentioning
confidence: 99%
“…NOACs have been considered to have lower risk of recurrent sICH compared with VKA (relative risk of 0.46). 47 As for antiplatelet therapy, there is conflicting evidence to whether it increases the risk of recurrent sICH. Some studies concluded that antiplatelet therapy increased the risk of recurrent sICH while others did not.…”
Section: Risk Of Recurrent Ichmentioning
confidence: 99%
“…В крупных рандомизированных исследованиях по ХСН выявлено, что распространенность ФП возрастает парал-лельно утяжелению функционального класса ХСН от 10% у больных с I-II ФК по NYHA до 50% у пациентов с IV ФК [12,13]. С другой стороны, в исследованиях по ФП частота встречаемости ХСН варьирует от 21 до 68% [14]. Среди популяции больных Фрамингемского исследования почти у 1 500 лиц старше 50 лет за период наблюдения было отмечено развитие ХСН, ФП или ХСН в сочетании с ФП.…”
Section: Introductionunclassified